Answer:
![\sqrt[6]{432}](https://tex.z-dn.net/?f=%5Csqrt%5B6%5D%7B432%7D)
Step-by-step explanation:
![\sqrt[3]{4}\cdot\sqrt{3}=4^{\frac{1}{3}}\cdot3^\frac{1}{2}=(2^2)^\frac{1}{3}\cdot3^\frac{1}{2}=(2^\frac{4}{3})^\frac{1}{2}\cdot3^\frac{1}{2}=(2^\frac{4}{3}\cdot3)^\frac{1}{2}=(2^4\cdot27)^\frac{1}{6}=432^\frac{1}{6}=\sqrt[6]{432}](https://tex.z-dn.net/?f=%5Csqrt%5B3%5D%7B4%7D%5Ccdot%5Csqrt%7B3%7D%3D4%5E%7B%5Cfrac%7B1%7D%7B3%7D%7D%5Ccdot3%5E%5Cfrac%7B1%7D%7B2%7D%3D%282%5E2%29%5E%5Cfrac%7B1%7D%7B3%7D%5Ccdot3%5E%5Cfrac%7B1%7D%7B2%7D%3D%282%5E%5Cfrac%7B4%7D%7B3%7D%29%5E%5Cfrac%7B1%7D%7B2%7D%5Ccdot3%5E%5Cfrac%7B1%7D%7B2%7D%3D%282%5E%5Cfrac%7B4%7D%7B3%7D%5Ccdot3%29%5E%5Cfrac%7B1%7D%7B2%7D%3D%282%5E4%5Ccdot27%29%5E%5Cfrac%7B1%7D%7B6%7D%3D432%5E%5Cfrac%7B1%7D%7B6%7D%3D%5Csqrt%5B6%5D%7B432%7D)
Answer:
x = - 1
Step-by-step explanation:
(8x + 12) = 3 ( multiply both sides by 4 to clear the fraction )
3(8x + 12) = 12 ( divide both sides by 3 )
8x + 12 = 4 ( subtract 12 from both sides )
8x = - 8 ( divide both sides by 8 )
x = - 1
The correct transformation is a rotation of 180° around the origin followed by a translation of 3 units up and 1 unit to the left.
<h3>
Which transformation is used to get A'B'C'?</h3>
To analyze this we can only follow one of the vertices of the triangle.
Let's follow A.
A starts at (3, 4). If we apply a rotation of 180° about the origin, we end up in the third quadrant in the coordinates:
(-3, -4)
Now if you look at A', you can see that the coordinates are:
A' = (-4, -1)
To go from (-3, -4) to (-4, -1), we move one unit to the left and 3 units up.
Then the complete transformation is:
A rotation of 180° around the origin, followed by a translation of 3 units up and 1 unit to the left.
If you want to learn more about transformations:
brainly.com/question/4289712
#SPJ1
Answer:
1350
Step-by-step explanation:
Hope this helps!